Serrated polyps: critical precursors to colorectal cancer. (September 2011) - Sweetser, Seth; Smyrk, Thomas C; Sugumar, Aravind
Colorectal polyps have been traditionally classified as either hyperplastic or adenomatous, with only the latter progressing to carcinoma. However, it is now recognized that certain subtypes of serrated polyps have a risk of malignant transformation via a serrated neoplasia pathway. Serrated polyps are a heterogeneous group of lesions with distinct morphologic, histologic and molecular genetics profiles. Based on available evidence, there are reasons to suspect that this pathway may contribute to interval or missed cancers because serrated lesions are more likely than conventional adenomas to be missed on colonoscopy, and the progression of serrated polyps to cancer may be more rapid. Therefore, it is paramount that physicians recognize the importance of serrated polyps and are aware of the latest surveillance guidelines.